Catholic Schools: The Inclusion of Non-Catholic Students - Donlevy, J. Kent (Canadian Journal of Education/Revue canadienne de l’éducation, 2002)
In this article, I examine the adequacy of a Catholic school district's written documents dealing with the inclusion of non-Catholic students. I first describe, in communitarian terms, the nature of a Catholic school community; then I use a contractarian analysis of the school district's written inclusionary policy to better understand its implications. The analysis illuminates several policy deficiencies for protecting the contractual and constitutional rights of both non-Catholic students and their parents. Suggestions are offered, pointing towards the creation of a new, meaningful inclusionary policy. Keywords: Catholic education, religious education, inclusion, non-Catholic schools Dans cet article, j’examine la pertinence des documents écrits d’une commission scolaire catholique au sujet de l’inclusion des élèves non catholiques. Je commence par décrire, en termes communitariens, la nature de la communauté que forme l’école catholique ; j’utilise ensuite une analyse contractualiste de la politique d’inclusion de la commission scolaire afin de mieux en comprendre les implications. L’analyse fait ressortir plusieurs lacunes de cette politique quant à la protection des droits contractuels et constitutionnels des élèves non catholiques et de leurs parents. Je formule des suggestions en vue d’une nouvelle politique inclusive digne de ce nom. Mots clés : Éducation catholique, éducation religieuse, inclusion, élèves non catholiques